2022
DOI: 10.3389/fpsyg.2022.949446
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of internet-delivered mindfulness-based stress reduction on mental health, self-efficacy, and body image among women with breast cancer during the COVID-19 pandemic

Abstract: Background and aimDuring the COVID-19 pandemic, an Internet-Mindfulness-Based Stress Reduction (iMBSR) program was delivered and may be better than an in-person approach. Our study evaluated the effects of iMBSR intervention on mental health, self-efficacy, and body image in women with breast cancer in Taiwan.Materials and methodsSixty-seven women with breast cancer were allocated to a 6-week iMBSR (n = 41) program or a waitlist control group (n = 26), without heterogeneity between group characteristics. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…The final sample for the systematic review included 17 intervention studies published during 2012–2023 (Table 1). Studies were conducted across various countries, including Iran ( n = 8) (Bahreini et al., 2022; Dokaneheei et al., 2016; Givehki et al., 2018; Moghadam et al., 2023; Moradi et al., 2020; Rahmani et al., 2014; Sharbaf Olyaie et al., 2016; Shirazipour, 2022), Sweden ( n = 2) (Fogelkvist et al., 2020; Weineland et al., 2012), Portugal ( n = 2) (Duarte et al., 2017; Pinto‐Gouveia et al., 2017), Australia (Sherman et al., 2018), India (Mukherjee & Ghosh, 2022), Taiwan (Chang et al., 2022), USA (Paterson, 2015) and a multinational study including Australia, New Zealand and United Kingdom (Mifsud et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The final sample for the systematic review included 17 intervention studies published during 2012–2023 (Table 1). Studies were conducted across various countries, including Iran ( n = 8) (Bahreini et al., 2022; Dokaneheei et al., 2016; Givehki et al., 2018; Moghadam et al., 2023; Moradi et al., 2020; Rahmani et al., 2014; Sharbaf Olyaie et al., 2016; Shirazipour, 2022), Sweden ( n = 2) (Fogelkvist et al., 2020; Weineland et al., 2012), Portugal ( n = 2) (Duarte et al., 2017; Pinto‐Gouveia et al., 2017), Australia (Sherman et al., 2018), India (Mukherjee & Ghosh, 2022), Taiwan (Chang et al., 2022), USA (Paterson, 2015) and a multinational study including Australia, New Zealand and United Kingdom (Mifsud et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…A variety of clinical populations belonging to different physical, psychological or psychiatric conditions were investigated in the included studies. Physical conditions included bariatric surgery (Weineland et al., 2012), breast cancer ( n = 8) (Chang et al., 2022; Mifsud et al., 2021; Moghadam et al., 2023; Mukherjee & Ghosh, 2022; Paterson, 2015; Rahmani et al., 2014; Sharbaf Olyaie et al., 2016; Sherman et al., 2018), polycystic ovary syndrome (PCOS) (Moradi et al., 2020) and obesity (Dokaneheei et al., 2016). Psychological or psychiatric conditions included binge eating disorder ( n = 2) (Duarte et al., 2017; Pinto‐Gouveia et al., 2017), eating disorder (Fogelkvist et al., 2020), depression (Shirazipour, 2022), psychosomatic disorder (Givehki et al., 2018) and body dysmorphic disorder (Bahreini et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical movement, meditation, and yogic breathing are some of the elements of the integrated yoga intervention that have been shown to elicit the relaxation response [ 67 ]. Yoga postures, breathing techniques, and their interconnections with mindfulness-based therapies have dramatically enhanced sleep efficiency caused by anxiety-related problems, and cancer sufferers [ 68 ]. Previous research has demonstrated that yoga is an effective stress management approach [ 2 ].…”
Section: Resultsmentioning
confidence: 99%